NEOLOGISMS OF THE COVID-19 PANDEMIC PERIOD IN THE ASPECT OF TRANSLATION (BASED ON ENGLISH AND GERMAN ONLINE MEDIA) - T.S. Medvedeva; A.M. Shakhmetova (Многоязычие в образовательном пространстве)
The article analyses the ways of translating from German and English into Russian the new words and phrases which emerged during the coronavirus pandemic. It presents the structural, semantic, and functional characteristics of 50 English neologisms and 50 German neologisms, selected by the continuous sampling method from online media in both languages. The study reveals the dominant role of calquing, as well as an increasing frequency of transcription and transliteration, indicating a desire for quick and accurate transmission of the meaning of new concepts in the Russian media. The tolerance for borrowed neologisms that retain their original form suggests a liberalisation of linguistic norms and a willingness to incorporate foreign language elements. The borrowing of the analytical word formation model typical of the English language indicates the influence of this language on the linguistic system of Russian. The smaller number of neologisms translated from German, compared to English, probably reflects the global role of English as a lingua franca in science, technology, and international communication.